Sequence analysis and expression of VP3 gene of chicken anaemia virus - M. S., Hasmah; Abdul Rahman, Omar; Ideris, Aini; Bejo, Mohd Hair (Veterinary Association Malaysia, 2003)
Chicken anaemia virus (CAV) isolate BL-5 VP3 gene was amplified, sequenced and expressed in E. coli as a fusion protein together with a six-histidine tag. The deduced amino acid sequence of VP3 was identical to other CAV isolates Cux-1, A2 and CIA-1 except for a single amino acid substitution at position 12. SDS-PAGE and Western blot analysis indicated that the expressed protein is insoluble and was found primarily from the cell lysate fraction. Expression of the protein was detected as early as 1 h, with maximum expression (~12% of the total protein) at 6 h post induction with IPTG. This study indicates that VP3 protein is highly expressed in insoluble form in E. coli. However, the biological function of the protein remains to be studied